2016
DOI: 10.4049/jimmunol.1600206
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell KLF2 Expression Regulates T Cell Activation and Proatherogenic Immune Responses

Abstract: Dendritic cells (DCs), have been implicated as important regulators of innate and adaptive inflammation in many diseases including atherosclerosis. However, the molecular mechanisms by which DCs mitigate or promote inflammatory pathogenesis are only partially understood. Previous studies have shown an important anti-inflammatory role for the transcription factor KLF2 in regulating activation of various cell types that participate in atherosclerotic lesion development, including endothelial cells, macrophages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Finally, KLF2 also plays a role in regulating the DC response during vascular inflammation. As is seen with monocytes and neutrophils ( 99 ), loss of KLF2 in DCs increases inflammatory cytokine production, DC tissue infiltration, and T-cell activation in atherogenic Ldlr − / − mice ( 100 ). Together, these studies further demonstrate that KLF2 largely opposes inflammatory activation in circulating immune cells.…”
Section: Klfs In Other Circulating Immune Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, KLF2 also plays a role in regulating the DC response during vascular inflammation. As is seen with monocytes and neutrophils ( 99 ), loss of KLF2 in DCs increases inflammatory cytokine production, DC tissue infiltration, and T-cell activation in atherogenic Ldlr − / − mice ( 100 ). Together, these studies further demonstrate that KLF2 largely opposes inflammatory activation in circulating immune cells.…”
Section: Klfs In Other Circulating Immune Cellsmentioning
confidence: 95%
“…Interestingly, a similar effect is seen with dendritic cell (DC)-specific KLF2 knockout. Loss of KLF2 in DCs aggravates atherosclerosis as a result of enhanced T-cell activation and heightened inflammatory cytokine production ( 100 ). Together, these studies demonstrate a central role of KLF2 in maintaining quiescence in circulating myeloid cells; a role it serves in ECs as well.…”
Section: Monocyte/macrophage Klfsmentioning
confidence: 99%
“…Abrogation of the mechanosensitive Kruppel-like factor 2 (KLF2) in CD11c + APCs promotes surface localization of the costimulatory molecules CD40 and CD86 and increased T cell proliferation and apoptosis. After Klf2 −/− bone marrow transplant to LDLR −/− mice, the absence of KLF2 increases the number of DCs in lesions, enhances T cell activation and cytokine production, and increases atherosclerotic lesions’ size [295]. APCs also mediate tolerogenic responses by reducing effector T cell functions and enhancing Treg functions [296,297].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Further study showed that the quiescent status of T cells is maintained through negatively regulated c-myelocytomatosis (Myc)/mitotic arrest deficient (Mad)-dependent pathways and by inducing expression of the cell cycle inhibitor p21 cip1 [ 19 ]. Study has shown that KLF2 deficiency stimulates surface expression of co-stimulatory molecules CD40 and CD86 in dendritic cells and increases T cell activation [ 20 ]. In addition to maintaining cellular quiescence, KLF2 also plays a critical role in controlling T cell trafficking from thymus to secondary lymphoid tissues by directly regulating CD62L, an adhesion receptor vital for T cell egress from the blood into secondary lymphoid tissues and Sphingosine 1-phosphate receptor 1 (S1P 1 ), a lysosphingo lipid receptor that regulates T cell trafficking from thymic and peripheral lymphoid tissue.…”
Section: Kruppel Like Factormentioning
confidence: 99%